A Clinical Case of Atrial Fibrillation with Coronary Vessel Ectasia - Rizaeva M.J. (Genius Journals, 2023)
Atrial fibrillation (AF) is one of the most common versions of supraventricular tachyarrhythmia that a doctor has to deal with in everyday practice [1,12]. It is believed that fibrillation is an independent risk factor for cardiovascular disease, because cardiac arrhythmia leads to a deterioration in the quality of life of patients, the possibility of thromboembolic complications, leading to sudden cardiac death. In the general population, AF in the adult population is 3% [2,13]. The prevalence of AF has now doubled compared to previous decades. The prevalence of AF varies with age, gender, and in the presence of structural heart disease
Keywords: Ectasia; ischemic heart disease; atrial fibrillation